PENYELESAIAN WANPRESTASI PT.PLN DENGAN WARGA PRASUNG KABUPATEN SIDOARJO: Studi Kasus Prasung Tani RT.01 RW.01 - Salfania, Muhamad Rengge; Octarina, Nynda Fatmawati (LPPM Universitas Bina Bangsa, 2024)
The background of this research is the agreement giving birth to an engagement or legal relationship that gives rise to rights and obligations for each party. Thus an agreement in the form of an agreement is essentially binding, even in accordance with Article 1338 paragraph 1 of the Civil Code, this agreement has binding power as a law for the parties who make it. The purpose of this study is to find out the terms of the agreement that resulted in default and settlement efforts between PT. PLN with residents of Prasung Tani Rw 01 RT 01 Sidoarjo Regency. This research method uses empirical juridical with a descriptive qualitative approach. The findings of this study indicate that in the agreement between PT PLN and PT Saba Prima with residents of the village of Prasung Tani RT 01 RW 01 Sidoarjo Regency there was a default that occurred. In the case of default that occurred in the Agreement between PT PLNand PTSaba Prima with residents of Prasung Tani village RT01 RW01 Sidoarjo Regency, there were several default settlements, namely the first party chose to go through the Non-Litigation route, namely through consensus deliberation with the villagers of Prasung Tani RT 01 RW 01 Regency Sidoarjo